Teachers’ Reinforcement on Students’ Behavior in English Teaching Process at the First Grade Sudents of SDIT Padang Islamic School in Academic Year 2018/2019 - Rosi Kumala Sari (Universitas Putra Indonesia YPTK Padang, 2021)
This study was a descriptive study aimed at describing the implementation of reinforcement used by English teacher to the students on the first grade of SDIT Padang Islamic School, Gunung Pangilun Padang. The subjects of this study were an English teacher and 24 students. The data of this study were collected by observation and interview. The result of this study showed that the English teacher on the first grade of SDIT Padang Islamic School, Gunung Pangilun Padang used various kinds of reinforcement such as verbal, gestural, contact, and proximity reinforcement. Positive and negative reinforcement were consisted by each of those types. For positive reinforcement, the teacher used “good, very good, well done, good enough, that‟s right, nice, smiling, nodding head, thumb up, applause, touching the students, standing next to the students, and sitting close with the students”. For negative reinforcement, the teacher used “sssst, calling students‟ name, giving warning, giving explanation, and putting forefinger in front of the lips”. Besides, the teacher also apply it enthusiasticly.